PEMERIKSAAN KESEHATAN PADA LANSIA DI DUSUN RINGINSARI BOKOHARJO PRAMBANAN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - TUTIK ASTUTI (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2021)
Background: Cervical cancer is the second cancer in the world that affects most women after breast cancer, especially in developing countries such as Indonesia. Factors that make the early detection done by women due to lack of knowledge about cervical cancer, for example to maintain the cleanliness of the female area (vagina) is very important, especially for women and how to detect early so that women are not affected by cervical cancer. Objective: To determine the differences in Pre and Post knowledge of Health Counseling about Cervical Cancer in Women in Ringinsari Bokoharjo Prambanan Sleman Special Region of Yogyakarta Method: The method used is a quasi experiment with the "One Groups Pretest-Posttest Design" approach. The number of samples is 35 people. Sampling in this study is using accidental sampling sampling technique. Results: Most (45.71%) pre test knowledge of cervical cancer and early detection in the less category and after being given counseling most (71.43%) were in the good category. Known p_value 0,000 <0,05. Conclusion: There is a difference between knowledge about cervical cancer before being given counseling and after being given counseling. Keywords: Extension, Cervical Cancer